Managerial economics: principles and worldwide applications - Srivastava, Ravikesh (Oxford University Press, 2009)
Managerial economics: principles and worldwide applications / Srivastava, Ravikesh. -- New Delhi: Oxford University Press, 2009 330 Sr774e6 6th ed No. of Copies : 1